Poverty - the world's deadliest disease ([s.n.] [S.l.], 1996)
Presents a selection of previously published articles on poverty, which are germane to the Conference on a New Global Human Order and Sustainable Development, Georgetown, Guyana, August 2-4, 1996.
DC